EDUKASI METODE MINDFUL JOURNALING DALAM PENINGKATAN STRATEGI MANAJEMEN STRES PADA REMAJA - Sanjiwani, Anak Agung Sri; Wati, Ni Made Nopita; Dewi, Ni Luh Putu Thrisna; Lisnawati, Ketut; Sudarma, Nyoman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2025)
Stress is one of the mental health problems that can be experienced by adolescents. The dynamics of the transition to adulthood can create various challenges for adolescents. This is also accompanied by high peer competition, environmental demands, the urge to show themselves and other factors making adolescents a vulnerable group related to mental health issues. Stress, even in the mild category, if unrecognized and untreated can lead to greater potential for mental health problems. Based on this, the community service activities carried out aim to provide education to adolescent students regarding strategies in managing daily stress and introduce one of the strategies that can be done for stress management by doing mindful journaling. The methods provided were lectures, discussions and writing simulations for 24 students at the vocational high school level. The results of the community service activities showed that there was an increase in knowledge after being given the material as well as the ability to identify stressors, thoughts-feelings and evaluate actions in dealing with the stressors faced through mindful journaling exercises.